1994
DOI: 10.1002/clc.4960170410
|View full text |Cite
|
Sign up to set email alerts
|

Torsade de pointes complicating drug treatment of low‐malignant forms of arrhythmia: Four case reports

Abstract: Summary:In patients with malignant ventricular arrhythmias, antiarrhythniic therapy is known to c x y a substantial risk of proarrhythmia. This risk is usually considered to be low when supraventricular arrhythmias or benign ventricular arrhythmias are considered. We were able to collect data on four patients without a history of life-threatening arrhythmias. in whom witiarrhythmic therapy was used and resulted in documented ventriculx fibrillation or torsade de pointes. In Cases No. 1 and 2.amal fibrillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…This study showed that attenuated bradycardia‐dependent prolongation of QT interval during AF was gradually corrected after restoration of SR from AF. This could be consistent with the finding that TdP developed a few hours after restoration of SR rather than immediately after restoration of SR . VR (SDQT/SDRR) as a measure of QT dynamics became greater at SR 4‐5h than at AF 4‐5h , and this could also be related to increases in risk of fatal arrhythmia after restoration of SR.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This study showed that attenuated bradycardia‐dependent prolongation of QT interval during AF was gradually corrected after restoration of SR from AF. This could be consistent with the finding that TdP developed a few hours after restoration of SR rather than immediately after restoration of SR . VR (SDQT/SDRR) as a measure of QT dynamics became greater at SR 4‐5h than at AF 4‐5h , and this could also be related to increases in risk of fatal arrhythmia after restoration of SR.…”
Section: Discussionsupporting
confidence: 85%
“…When such drugs are used to treat atrial fibrillation (AF), TdP could develop after restoration of sinus rhythm (SR); however, this rarely happens when the underlying rhythm remains in AF . TdP could occur a few hours after rather than immediately after restoration of SR, when AADs that prolong QT interval are given …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the small number of cases, a causation between the medication and the induction of Tdp thus seems likely, though the exact proarrhythmic mechanism remains unclear. Yet, several investigators found an increased proarrhythmia risk associated to therapy with antiarrhythmic agents in combination with heart rate suppressing drugs, 12 , 21 supporting our thesis. Patients with chronic heart failure are nowadays more likely to be treated with such combination therapies of two or more cardiovascular and/or antiarrhythmic drugs.…”
Section: Discussionsupporting
confidence: 80%
“…In the case of an inappropriately short QT interval after AF conversion, the potential protective effect of a longer QT interval at lower heart rates is transiently abolished. It seems possible that reentrant and polymorphic tachyarrhythmias could be facilitated in this situation, an effect which may become of crucial importance when the additional influence of sotalol is considered [9].…”
Section: Discussionmentioning
confidence: 99%